ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA SMP DALAM PEMBELAJARAN PENDIDIKAN TEKNOLOGI DASAR (PTD) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2013)
Research on creative thinking abilities of students have been carried out in learning Basic Technology Education (BTE). This research was stimulated by the present issues which concern in the development of creativity that less attention in formal education. Thus creativity is very meaningful to the development of self actualization potential of students as a whole. This study aims to gain an overview of creative thinking abilities of students in one of junior high schools in Bandung. The research method used is descriptive method. The sample in this study is one of the 8th grade consisting of 26 students which was selected by purposive sampling. Data was collected using an instrument that tests the ability to think creatively about the form of essay. Results showed that students' creative thinking ability in learning BTE dividedinto three categories, namely, the category of high, medium, and low. The category of creative thinking ability of students in learning, most dominated by medium category. The highest percentage of creative thinking ability characteristics is originality thinking skills and the smallest average percentage is the elaboration skills. Related to student achievement, there is an increase in student achievement after BTE learning to the acquisition by 0.43 in medium category.Telah dilakukan penelitian mengenai kemampuan berfikir kreatif siswa dalam Pembelajaran Pendidikan Teknologi Dasar (PTD) yang distimulasi dari munculnya isu bahwa perkembangan kreativitas anak kurang diperhatikan dalam pendidikan formal, padahal kreativitas sangat penting dalam perkembangan potensi siswa. Penelitian ini bertujuan untuk meningkatkan kemampuan berfikir kreatif siswa di salah satu SMP di Kota Bandung. Penelitian ini adalah penelitian deskriptif. Sampel dalam penelitian ini adalah salah satu kelas 8 yang terdiri dari 26 siswa yang dipilih dengan menggunakan metode purposive sampling. Data dikumpulkan dengan menggunakan instrumen yang mengukur kemampuan berfikir kreatif dengan berbentuk essay. Hasil menunjukkan bahwa kemampuan berfikir kreatif dalam pembelajaran PTD dibagi menjadi tiga kategori yaitu tinggi, sedang dan rendah. Kemampuan berfikir kreatif siswa yang dominan adalah dalam kategori sedang. Persentase karakteristik kemampuan berfikir kreatif yang tertinggi yaitu originality dan yang terendah yaitu elaboration. Sedangkan mengenai prestasi siswa, ada peningkatan dalam prestasi siswa setelah diterapkan pembelajaran PTD dengan gain yang dinormalisasi sebesar 0,43 dengan kategori sedang.
Keywords: kemampuan berfikir kreatif; pembelajaran PTD; prestasi belajar; BTE learning,; creative thinking ability; student’s achievement